2020
DOI: 10.21203/rs.3.rs-96736/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Maternal and Perinatal Health: A Scoping Review

Abstract: Introduction: Maternal health is a critical public health issue, and the Coronavirus Disease 2019 (COVID-19) pandemic has had a multifaceted impact on the health and wellbeing of pregnant individuals and mothers. Methods: A scoping review was conducted to compile evidence on direct and indirect impacts of the pandemic on maternal health and provide an overview of the most significant outcomes thus far. Working papers and news articles were considered appropriate evidence along with peer-reviewed publications i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 55 publications
0
31
0
1
Order By: Relevance
“…Mothers are at greater risk than fathers for loss of employment and reduced work hours during the COVID-19 pandemic. 11 Despite one quarter of our sample losing their job or reducing their work hours (24.7%), this factor was not related to more household chaos. While reduced work hours allow for more time to be dedicated to caregiving, the potential adverse effects on household chaos may take longer to materialize.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Mothers are at greater risk than fathers for loss of employment and reduced work hours during the COVID-19 pandemic. 11 Despite one quarter of our sample losing their job or reducing their work hours (24.7%), this factor was not related to more household chaos. While reduced work hours allow for more time to be dedicated to caregiving, the potential adverse effects on household chaos may take longer to materialize.…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, many women reported disruption to their daily lives from the COVID-19 pandemic, namely, in their childcare duties and employment status, which has been demonstrated in mothers in other countries. 11,12 Finally, one limitation is the current sample was recruited through listservs, social media, and other electronic means, and may be at risk for more distress from pandemic-related media exposure compared to others. 34 Considering current stress in this sample (6.9 ± 1.9, May 2020) is comparable to a Canadian sample of 253 mothers of young children during the pandemic who were recruited without social media methods (6.8 ± 1.9, April 2020), 10 it may be that mothers' stress levels are high regardless of recruitment strategy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While half of the pregnant women indicated that the pandemic affected their ongoing pregnancy experience, only a minority of breastfeeding women felt that COVID-19 had an impact on how they personally dealt with breastfeeding. As reflected by the quotations and described elsewhere [ 42 , 43 ], pregnant women attributed their negative experience to the reduced medical follow-up, the absence of the partner during antenatal care visits and increased anxiety or stress due to the current situation. Overall, breastfeeding women generally denied that the pandemic influenced their breastfeeding practices.…”
Section: Discussionmentioning
confidence: 99%